Analisis Penggunaan Pembangkit Listrik Tenaga Surya Sebagai Suplai Cadangan Energi Pada Mesin Mixer Donat (Studi Kasus Di CV Youlanda) - Bimo Duta Pangestu; Dino Erivianto; Muhammad Erpandi Dalimunthe (CV. Hawari, 2025)
The need for stable electricity supply is a major challenge for Micro, Small, and Medium Enterprises (MSMEs), especially when disruptions occur in the main grid. This study examines the utilization of a small-scale Solar Power Generation System (PLTS) as a backup energy source to operate a donut mixer machine at CV Youlanda. The system consists of two solar panels with a combined power of 40 Wp, two 12V 8Ah batteries, a 1000W inverter, and a 20A charge controller (SCC). The research was conducted through direct field measurements to assess the performance and efficiency of the system under varying weather conditions. The observations show that in sunny weather, the system can generate about 200 Wh per day, which is sufficient to run two cycles of the mixer. The actual energy consumption per cycle was measured at 65.61 Wh. The total system efficiency was 2.63%, including panel efficiency of 8%, battery storage efficiency of 77%, and load efficiency of 42.71%. However, in cloudy weather, the available energy is only enough for about 8 minutes of operation. These findings indicate that, despite its limitations, small-scale PLTS remains a viable alternative energy solution that is cost-effective, environmentally friendly, and suitable for light operational needs in the MSME sector.